Low-temperature hydrothermal synthesis single-crystal ZnO nanowire for gas sensor application. (2018) - Tuscharoen, S.; Kulakeatmongkol, N.; Horprathum, M.; Aiampanakit, K.; Eiamchai, P.; Pattantsetakul, V.; Limwichean, S.; Chananonnawathorn, C.; Hendro; Kaewkhao, J.
Abstract: Single-crystal zinc oxide nanowires (ZnO NWs) were successfully fabricated by low-temperature hydrothermal method using zinc acetate and hexamethulenetramine. The possible grown mechanism of the influence of precursor concentration on ZnO NWs was discussed in the detail. The as-grown single crystal ZnO NWs structural were investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM) and field-emission scanning electron microscopy (FE-SEM). The XRD and TEM resulted showed that the structure of ZnO NWs was wurtzite structure. The growth rate and morphology of ZnO NWs was depended on the precursor concentration. Furthermore, their hydrogen gas sensing characteristics were systematically investigated and discussed in this paper.